User preferences for future electric vehicle charging infrastructure: A Stated Choice Experiment for Danish EV users : udvidet resumé - Visaria, Anant Atul (Proceedings from the Annual Transport Conference at Aalborg University, 2020)
While the adoption EVs is rapidly growing, the global EV stock is still less than 1% of car fleet. It is expected that in coming years, with improved technology, the battery size and in turn the EV driving range will increase. The fact that EV prices will reduce over time and many countries intend to set up policies to support the purchase and use of EVs, it is expected that the EV adoption rate will continue to increase. However, this also means that there’s a need for better planning, especially for the charging infrastructure, to improve and support the transition to e-mobility. There is a strong behavioral and social aspect associated with the use of electric vehicles. This study tries to develop a qualitative and quantitative understanding of the most relevant aspects. The findings presented in this paper focuses on understanding the preferences of Danish EV users.